Mouse vs. cat in Chinese literature : tales and commentary - Idema, W. L. (Wilt L.); Lee, Haiyan (University of Washington Press, 2019)
"Wilt Idema presents Chinese tales about cats and mice, situating them in the Chinese literary tradition as a whole, and within Chinese imaginative depictions of animals. In the literatures of the ancient and modern Near East, South Asia, and medieval Europe, animal fables exhibited a range of anthropomorphic views, but Chinese literature is notable for its relative paucity of extended animal tales and rarity of talking animals. From ancient Egypt to China, rodents have long been vilified as thieves of grain in agrarian society, in perennial war with felines. Through varied depictions of the cat-mouse relationship, this set of tales allows to reader to consider the metaphorical roles of these animals in the Chinese literary imagination and to ponder their unusually prominent--and verbal--role in these stories. Of central focus is the legal case of the mouse against the cat in the underworld court of King Yama, a popular topic in the traditional ballad literature of late-imperial China and of present-day Chinese folk literature. Idema traces the development and variations of this theme of mice and cats in classical literature; to other stories of mice and cats in traditional vernacular literature; and to stories about the wedding of the mouse to the cat and the war between mice and cats. An epilogue traces the treatment of enmity between rodents and felines worldwide, and a foreword by Haiyan Lee explores the relevance of these tales to posthumanist consideration of human-animal relations. This entertaining volume will appeal to readers interested in Chinese literature and society, comparative literature, and animal studies in the humanities"--